Solid Phase Extraction and Flame Atomic Absorption Spectrometry for the Determination of Cobalt - Feng, Shaoping; Huang, Zhangjie; Li, Pengwei (Asian Journal of Chemistry, 2010)
A solid phase extraction and flame atomic absorption spectrometry for the determination of cobalt with SEPABEADS SP825 resin as sorbent was studied. Cobalt complexed with 2-ethylhexyl benzimidazolyl sulfide (EHBMS) was preconcentrated on a nonpolar resin SEPABEADS SP825 and 2-methoxyethanol was used as eluent. The effects of various parameters such as acidity, flow rate of sample and eluent, type of eluent, amount of adsorbent and interfering ions have been studied. The cobalt in 300 mL solution can be concentrated to 5.0 mL, representing an enrichment factor of 60 was achieved. The detection limit for 300 mL of sample was 0.16 μg L-1 using flame atomic absorption spectrometry. The analytical result for the certified reference sample (GBW07301a) was in a good agreement with the certified value. The relative standard deviation for ten replicate measurements of 10 μg L-1 cobalt was 2.9 %. The method was successfully applied to the determination of trace amount cobalt in water samples.